Dengue Viral Myositis Complicated with Rhabdomyolysis and Superinfection of Methicillin-Resistant Staphylococcus aureus - Vinothan Sunderalingam; Thirumavalavan Kanapathipillai; P. A. S. Edirisinghe; K. M. M. P. Dassanayake; I. H. G. S. Premawansa (Case Reports in Infectious Diseases)
Dengue is endemic in Sri Lanka and the physician should be aware of different and unusual presentation of the illness. Rhabdomyolysis is a well-known complication following many viral and bacterial infections; however, only a few cases have been reported with dengue viral infections. Further occurrence of coinfection by dengue and bacteria such as methicillin-resistant Staphylococcus aureus (MRSA) has been underestimated, and few reports have been published so far. This case describes a 17-year-old boy who presented with prolonged severe myalgia, dark red urine, and a febrile illness that was diagnosed as having dengue viral myositis, dark red urine, and a febrile illness that was diagnosed as having dengue viral myositis complicated with rhabdomyolysis and superinfection of MRSA. Despite intensive care management, he died due to multiorgan failure. Autopsy and serological studies confirmed the diagnosis. This case stresses that red-coloured urine in dengue patients is not always due to haematuria, and if a patient’s vital signs do not respond to appropriate fluid management in DHF, sepsis from a secondary pathogen including MRSA should be suspected.